1186 Audit Driven Standardisation Of Perioperative Risk Profiling in Carotid Endarterectomy. (12th October 2021) - Muhammad, K; Al-Khaffaf, H
Abstract: Introduction: It is a fundamental good clinical practice in our medicolegal rights era to obtain standard, adequate, and transparent informed consent before any planned intervention. Currently, there are neither national approved vascular intervention-specific consents nor explicit guidelines for it. We aim to achieve a standardisation of perioperative risk profiling of carotid endarterectomy consents and produce a model one. Method: A retrospective analysis of 65 carotid endarterectomy consents (audit/reaudit) between (2016-2019) retrieved to evaluate quality and completeness against GMC 2008 guidance: "Consent: patients and doctors making decisions together". Data included basic consent requirements according to guidelines and speciﬁc risks of carotid endarterectomy. It was registered with the Trust Clinical Audit Department. Results: (90%) audit vs (87%) reaudit consents documented the intended benefits of surgery. Inclusion into the National Vascular Registry (NVR) was achieved (0%) in audit vs (60%) in reaudit forms. Of the 14 documented postoperative complications, reaudit significant improvement observed in % of documenting 12 items with 6 complications recorded above 50%. The maximum number of audit documented risks was 11 (79%), the median 6 (43%), and the least was 3 (21%) compared to maximum 13 (93%), the median 7 (50%) and the least was 5 (36%) when reaudited, respectively. Conclusions: Deficiencies in performing and adequately completing surgical consents still occur. Introducing a national pre-printed vascular intervention-specific consent is vital for accomplishing and maintaining a good clinical practice. It should include all complications with relative % risk to minimise errors, provide good quality consent, and promote clinical practice at a national level.